The importance of epigenome research in the diagnosis and treatment of endometriosis - Wirstlein, Przemysław Krzysztof; Jagodziński, Paweł P.; Szczepańska, Małgorzata (Journal of Medical Science, 2017)
The causes of endometriosis remain unexplained. Studying the molecular mechanisms at the origin of the lesions leads to conclusions about the important role of the epigenome. This mini-review is a summary of the current state of knowledge about the processes of epigenetic control of gene expression involved in the pathogenesis of endometriosis.
Keywords: endometriosis; gene expression; methylation